Probio Blends / Allisha Mohd Nur Ismal ... [et al.] - Mohd Nur Ismal, Allisha; Shafeai, Nurul Aleya Natasha; Ahmad, Anisa Humaira; Fisol, Nur Izzah Athirah; Jisan, Zizie Azzarina (2025)
ProBio Blends, based in Malaysia, specializes in crafting high-quality probiotic smoothies designed to promote digestive health and overall well-being. With operations spanning two key locations, a state-of-the-art factory in Pulau Indah, Klang for efficient production and a vibrant retail shop in Sunway Pyramid Mall dedicated to delivering fresh, nutrient-packed smoothies to its customers. Our concept of product is a smoothie in a soft, creamy texture which is made from healthy delicious fruits and enriched with good gut health’s bacteria. Our objective is to create a drink that can maintain gut health at an affordable price and make it a well-known brand across the world. Our main product consists of delicious and nutritious probiotic smoothies created with premium, organic, and fresh ingredients. These smoothies are specifically designed to improve bacteria in the intestinal tract, support digestive health, and increase immunity. We provide a range of size and flavours to satisfy various consumers preferences. Our target market focuses on health-conscious individuals aged 18-35, including students, young professionals, and fitness enthusiasts, who seek convenient, nutritious, and affordable options to complement their active lifestyles. By using locally sourced, fresh, and organic ingredients, ProBio Blends meets the growing demand for functional beverages while supporting sustainable and healthy living.